Penguatan Etika Politik Pancasila di Era Digital - Ronni Juwandi; Yoga Adi Febrian (Proceeding of the International Conference on Global Education and Learning, 2025)
This article discusses the urgency of strengthening Pancasila-based political ethics in addressing the challenges of the digital era. Pancasila, as the foundation of the state and a source of public ethics, faces various distortions in digital political practices, such as social media polarization, the spread of hoaxes, and the manipulation of public opinion. In this context, the values of Pancasila—particularly unity, social justice, and deliberation—serve as the moral foundation that must be reinforced through digital literacy and inclusive public policies. The discussion in this paper includes the concept of political ethics, the relevance of Pancasila values in digital spaces, strategies for strengthening these values through digital literacy curricula and public campaigns, and examples of implementation in digital policies and the behavior of online political actors. Using a normative and applicative approach, this paper emphasizes the importance of collaboration between the government, society, and media in creating an ethical and democratic digital ecosystem. Strengthening Pancasila-based political ethics is expected to foster a moral, critical, and inclusive Indonesian digital society.